IL-1β suppresses TGF-β-mediated myofibroblast differentiation in cardiac fibroblasts. (June 2013) - Brønnum, Hasse; Eskildsen, Tilde; Andersen, Ditte Caroline; Schneider, Mikael; Sheikh, Søren Paludan
Abstract Cardiac fibrosis is a maladaptive response of the injured myocardium and is mediated through a complex interplay between molecular triggers and cellular responses. Interleukin (IL)-1β is a key inflammatory inducer in cardiac disease and promotes cell invasion and cardiomyocyte injury, but little is known of its impact on fibrosis. A major cornerstone of fibrosis is the differentiation of cardiac fibroblasts (CFs) into myofibroblasts (myoFbs), which is highly promoted by Transforming Growth Factor (TGF)-β. Therefore, we asked how IL-1β functionally modulated CF-to-myoFb differentiation. Using a differentiation model of ventricular fibroblasts, we found that IL-1β instigated substantial anti-fibrogenic effects. In specific, IL-1β reduced proliferation, matrix activity, cell motility and α-smooth muscle actin expression, which are all hallmarks of myoFb differentiation. These findings suggest that IL-1β, besides from its acknowledged adverse role in the inflammatory response, can also exert beneficial effects in cardiac fibrosis by actively suppressing differentiation of CFs into fibrogenic myoFbs.